Victims' emotional distress and preventive measures usage: Influence of crime severity, risk perception, and fear. (10th July 2019) - Chadee, Derek; Williams, Diana; Bachew, Raecho
Abstract: The central thesis of this study is that crime victims' emotional distress, influenced by the severity of the offence experienced, impacts their propensity to utilize preventive measures via its influence on perceived risk of victimization and fear of crime. Path analysis was conducted to test a model of these relationships, utilizing data from a crime victimization survey conducted on the Caribbean Island, Trinidad, in 2015. Results suggest a direct predictive relationship between crime severity and emotional distress and indirect effects of emotional distress on preventive measures through risk perception and fear of crime. Findings were discussed in the context of prior research, comparability, and variances, and practical implications were noted.